Prevalence of Genes Encoding Bi-Component Leukocidins among Clinical Isolates of Methicillin-Resistant Staphylococcus aureus - SA Havaei; S Ohadian Moghadam; MR Pourmand; J Faghri (Tehran University of Medical Sciences, 2010)
"nBackground: Staphylococcus aureus has been recognized as a major human pathogen and is the major cause of nosocomial infections. Gamma-toxin, leukocidin and other bi-component toxins are a family of proteins encoded by the hlg and luk-PV, respectively. Panton-Valentine leukocidin (PVL) is an example of these toxins and causes leukocyte destruction and tissue necrosis. The aim of this study was to determine the prevalence of bi-component leukocidin in Methicillin - Resistant Staphylococcus aureus (MRSA) isolates in staphylococcal infections."nMethods: Collectively, 143 isolates of S. aureus were obtained from Tehran University of Medical Sciences hospitals and confirmed with biochemical tests. Then polymerase chain reaction was used to detect luk-PV loci and luk-E/D. Coagulase gene was used as internal control. The antibiotic susceptibility patterns of isolates were determined using disk diffusion method."nResults: Out of 149 S. aureus isolates 24.2% were luk-PV positive and 73.8% were luk-E/D positive."nConclusion: There was PVL-positive MRSA isolates with high prevalence in evaluated hospitals. The diseases from these bacteria are with extensive necrosis, leucopenia and even death. We desire that, prevent from progress and death by diagnosis and right treatment.